Relation Among Body Mass Index, Exercise Training, and Outcomes in Chronic Systolic Heart Failure - Horwich, Tamara B.; Broderick, Samuel; Chen, Leway; McCullough, Peter A.; Strzelczyk, Theresa; Kitzman, Dalane W.; Fletcher, Gerald; Safford, Robert E.; Ewald, Gregory; Fine, Lawrence J.; Ellis, Stephen J.; Fonarow, Gregg C. (The American journal of cardiology, 2011)
Exercise training (ET) in patients with heart failure (HF), as demonstrated in the Heart Failure: A Controlled Trial Investigating Outcomes of Exercise TraiNing (HF-ACTION), was associated with improved exercise tolerance and health status and a trend toward reduced mortality or hospitalization. The present analysis of the HF-ACTION cohort examined the effect of ET in overweight and obese subjects compared to normal weight subjects with HF. Of 2,331 subjects with systolic HF randomized to aerobic ET versus usual care in the HF-ACTION, 2,314 were analyzed to determine the effect of ET on all-cause mortality, hospitalizations, exercise parameters, quality of life, and body weight changes by subgroups of body mass index (BMI). The strata included normal weight (BMI 18.5 to 24.9 kg/m 2), overweight (BMI 25.0 to 29.9 kg/m 2), obese I (BMI 30 to 34.9 kg/m 2), obese II (BMI 35 to 39.9 kg/m 2), and obese III (BMI ≥40 kg/m 2). At enrollment, 19.4% of subjects were normal weight, 31.3% were overweight, and 49.4% were obese. A greater BMI was associated with a nonsignificant increase in all-cause mortality or hospitalization. ET was associated with nonsignificant reductions in all-cause mortality and hospitalization in each weight category (hazard ratio 0.98, 0.95, 0.92, 0.89, and 0.86 in the normal weight, overweight, obese I, obese II, and obese III categories, respectively; all p >0.05). Modeled improvement in exercise capacity (peak oxygen consumption) and quality of life in the ET group was seen in all BMI categories. In conclusion, aerobic ET in subjects with HF was associated with a nonsignificant trend toward decreased mortality and hospitalization and a significant improvement in quality of life across the range of BMI categories.